STRATEGI GURU PAI DALAM MENINGKATKAN DOMAIN KOGNITIF SISWA BERBASIS PEMBELAJARAN DARING PADA MASA PANDEMI COVID – 19 DI SMPN 05 KARANGPLOSO KABUPATEN MALANG - Shinta Margaretta; Khoirul Asfiyak; Indhra Mustofa (VICRATINA, 2021)
Various kinds of research on the theme of strategies to improve students' cognitive domains have been carried out, but in online-based learning during the Covid-19 pandemic, of course, it is still rare. This study aims to determine and increase knowledge in using learning strategies to improve students' cognitive domains in online learning during the Covid-19 pandemic. Using descriptive and in-depth research by interviewing PAI teachers from grades VII, VII, and IX as well as school principals, and waka curriculum. The results of the research regarding the teacher learning process are in accordance with the standard process by referring to the lesson plans and syllabus, the strategies used by teachers in online learning during the Covid-19 pandemic by using direct learning strategies (expositions), expository learning strategies, CTL strategies (contextual) , door to door strategy, Using the lecture method, supporting factors There may be main components (teachers, students, infrastructure) in the learning process that causes learning to still take place, The existence of books as learning resources, The existence of learning quota assistance from the government, Availability of applications online learning, there are still many students who have the intention to learn. Inhibiting factors can be as follows: Constrained signals for some students who live in difficult signal areas, Lack of parental support in supervising learning at home, Unable to face to face in learning so that it is not optimal in delivering material, Difficult to correct when practical material such as prayer practice, Koran etc., The lack of student motivation in learning, The lack of knowledge of students about online learning applications such as zoom, meet etc., There are some students who are constrained in the family economy so that for gadget problems they have to take turns with their parents who are used to work, and are constrained in internet quota as well .